Toothbrush design appropriate for pre-elderly: The relationship of toothbrush bristles number to oral hygiene - Suhartini, Suhartini; Hamzah, Zahreni; Setyaningsih, Sari; Prijatmoko, Dwi; Harmono, Happy; Arina, Yuliana Mahdiyah Daat; Prihatiningrum, Berlian (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The increase in the elderly population leads to a decline in their health and affects the productivity and quality of life. Preventive measures must be taken to improve oral hygiene for the elderly starting from the pre-elderly group so that later it will form healthy and productive elderly. One of the efforts to improve dental hygiene and health is through mechanical tooth cleaning with a toothbrush. However, currently, there is no toothbrush design that is suitable for the condition of the pre-elderly oral cavity. Therefore, it is necessary to analyze the design of the number of toothbrush bristles as initial research to obtain an appropriate toothbrush design for the elderly. Method:The study was conducted on 30 participants using a toothbrush with a number of toothbrush bristles paths: with 4 paths, 3 paths, and 2 paths. The effectiveness of tooth brushing hygiene was measured through the debris index before using a toothbrush and after brushing. Result: The results of the Kruskal Wallis test showed a significance value of 0.01 (p